Mental health practice in a digital world : a clinicians guide - Dewan, Naakesh A.; Luo, John S.; Lorenzi, Nancy M. (Health Informatics, 2015)
This book guides clinicians in critically evaluating and embracing well-designed and validated technologies that have the potential to transform the access, affordability, and accountability of mental healthcare. The reader will become aware of the practical applications of technology in mental health as well as research supporting information technology tools and policy debates. Each chapter contains either examples or scenarios that are relevant to the current practice of mental health care. Mental Health Practice in a Digital World: A Clinicians Guide is a key resource for current and future mental health clinicians who wish to become familiar with technology innovations and how they impact and improve clinical care. It contains chapters written by policy makers, application developers, scientists, and executives that have led or supported the use of technologies in real world practice.